Reinforced Calcium phosphate cements with zinc by changes in initial properties: A molecular dynamics simulation. (February 2023) - Banawas, Saeed; Ibrahim, Talib K.; Tlili, Iskander; Le, Quynh Hoang
Abstract: Calcium phosphate cement (CPC) has wide applications in medicine and dentistry, such as dental pulp coating, tooth root canal sealant, bone tissue engineering scaffolds, drug release systems, bone defect restoration, etc. Zinc nanoparticles, on the other hand, have special qualities that cause to provide the initial strength in CPC. The influence of starting temperature and beginning pressure on the thermal behavior (TB) and mechanical behavior (MB) of reinforced CPC was examined in this work using a molecular dynamics (MD) simulation. So, it was investigated how properties like temperature stability, Young's modulus, and ultimate strength changed. The mechanical stability of the simulated structure decreases from 300 K to 400 K at the starting temperature. In actuality, the force of absorption between the simulated structures has reduced as the temperature of the samples has risen. Additionally, the findings demonstrated that the US and YM underwent a downward trend and declined from 1.07 to 0.19 MPa to 0.89 and 0.16 MPa, respectively, when the starting temperature increased from 300 to 400 K. As a result, increasing the initial pressure reduces the inter-atomic distance in the reinforced matrix, and finally, cement particles absorb each other with a greater force.